Natural Transformation in Deinococcus radiodurans: A Genetic Analysis Reveals the Major Roles of DprA, DdrB, RecA, RecF, and RecO Proteins - Ithurbide, Solenne; Coste, Geneviève; Lisboa, Johnny; Eugénie, Nicolas; Bentchikou, Esma; Bouthier de la Tour, Claire; Liger, Dominique; Confalonieri, Fabrice; Sommer, Suzanne; Quevillon-Cheruel, Sophie; Servant, Pascale (Frontiers in Microbiology, 2020)
Horizontal gene transfer is a major driver of bacterial evolution and adaptation to environmental stresses, occurring notably via transformation of naturally competent organisms. The Deinococcus radiodurans bacterium, characterized by its extreme radioresistance, is also naturally competent. Here, we investigated the role of D. radiodurans players involved in different steps of natural transformation. First, we identified the factors (PilQ, PilD, type IV pilins, PilB, PilT, ComEC-ComEA and ComF) involved in DNA uptake and DNA translocation across the external and cytoplasmic membranes and showed that the DNA-uptake machinery is similar to that described in the Gram negative bacterium Vibrio cholerae. Then, we studied the involvement of recombination and DNA repair proteins, RecA, RecF, RecO, DprA and DdrB into the DNA processing steps of D. radiodurans transformation by plasmid and genomic DNA. The transformation frequency of the cells devoid of DprA, a highly conserved protein among competent species, strongly decreased but was not completely abolished whereas it was completely abolished in ΔdprA ΔrecF, ΔdprA ΔrecO, and ΔdprA ΔddrB double mutants. We propose that RecF and RecO, belonging to the recombination mediator complex, and DdrB, a specific deinococcal DNA binding protein, can replace a function played by DprA, or alternatively, act at a different step of recombination with DprA. We also demonstrated that a ΔdprA mutant is as resistant as wild type to various doses of γ-irradiation, suggesting that DprA, and potentially transformation, do not play a major role in D. radiodurans radioresistance.